TECHNICAL POSSIBILITIES OF TELEVISION AS A MEAN OF CREATING VIRTUALITY - Elena Nikolaevna Larionova (Вестник Северо-Кавказского федерального университета)
This article considers the basic techniques for creating television works (videoshooting, lighting, edit- ing), allowing to form the virtual space and virtual time through television text.